Mode of action of plant hormones and plant growth regulators during induction of somatic embryogenesis: molecular aspects - Jiménez García, Víctor (2005)
Plant hormones play critical roles in the establishment of somatic embryogenesis. During this process, somatic plant cells reverse their state of differentiation, acquire pluripotentiality and set up a new developmental program. The identification of the regulatory mechanisms that govern the key events of somatic embryogenesis requires molecular and genetic investigations. One critical issue is how plant hormones and growth regulators act to mediate somatic embryogenesis. Do they function as simple stimuli or participate directly, as central signals, in the reprogramming of the somatic cells towards an embryogenic fate? The latter scenario is now well supported by a number of studies that provide evidence of close interconnections between plant hormones and the molecular pathways that control somatic embryogenesis, including chromatin remodeling, gene expression patterning, reactivation of cell cycle and division and regulation of protein turnover. In this chapter we describe recent advances in the understanding of molecular and genetic mechanisms underlying the early stages of somatic embryogenesis. The roles and mode of action of plant hormones are especially emphasized.